Cecal Mucosal Myxoma: The First Report of a New Type of Mesenchymal Colon Polyp. (September 2019) - Bsirini, Caroline; Findeis-Hosey, Jennifer J.; Huber, Aaron R.
Myxomas are benign mesenchymal neoplasms of unknown etiology that most commonly occur in the cardiac atrium; however, other reported sites include the skin, joints, skeletal muscles, maxillofacial bones, and sinonasal tract. Myxomas involving the gastrointestinal (GI) tract are rare and are limited to a few published case reports. We are presenting, to our knowledge, the first case report of a mucosal myxoma in the colon presenting as a colonic polyp. A 49-year-old woman underwent a screening colonoscopy and was found to have a 0.2-cm sessile polyp in the cecum. Histologically, the polyp was composed of bland spindled cells in the lamina propria set in a hypocellular, myxoid stroma. The lesion was relatively well-demarcated from the surrounding mucosa. The overlying colonic epithelium showed no dysplasia. S-100 immunohistochemical stain showed only focal nonspecific positivity, while CD34, CD117, SMA, EMA, and desmin were all negative. Alcian blue special stain showed positive staining, supporting the diagnosis of myxoma. Myxomas in the GI tract are very rare, with this being the first reported case of a polypoid colonic mucosal myxoma. Previous reports of GI myxomas are limited to examples in the stomach, small bowel, and one recently reported case in the colon, all of which were submucosal lesions and not limited to the mucosa. In some of the prior reports, the patients had synchronous cardiac atrial myxomas. Mucosal colonic myxoma represents a newly identified mesenchymal polyp of the colon and pathologists should be aware of this diagnostic entity.